2005
DOI: 10.1017/s0033822200035220
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Capture Using a Zeolite Molecular Sieve Sampling System for Isotopic Studies (13C and 14C) of Respiration

Abstract: A method for collecting an isotopically representative sample of CO2 from an air stream using a zeolite molecular sieve is described. A robust sampling system was designed and developed for use in the field that includes reusable molecular sieve cartridges, a lightweight pump, and a portable infrared gas analyzer (IRGA). The system was tested using international isotopic standards (13C and 14C). Results showed that CO2 could be trapped and recovered for both δ13C and 14C analysis by isotope ratio mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
136
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(138 citation statements)
references
References 36 publications
2
136
0
Order By: Relevance
“…We employed the MSC previously described by Hardie et al (2005) and , and illustrated schematically in Fig. 1 Gut et al, 1998); air was free to pass from the atmosphere through the filter into the MSC, however, the filter prevented entry of liquid water.…”
Section: Molecular Sieve Cartridge (Msc) Design and Procedures -4 -mentioning
confidence: 99%
See 1 more Smart Citation
“…We employed the MSC previously described by Hardie et al (2005) and , and illustrated schematically in Fig. 1 Gut et al, 1998); air was free to pass from the atmosphere through the filter into the MSC, however, the filter prevented entry of liquid water.…”
Section: Molecular Sieve Cartridge (Msc) Design and Procedures -4 -mentioning
confidence: 99%
“…Zeolite molecular sieve is an extremely effective CO 2 absorbent that does not suffer from many of the disadvantages that affect hydroxides. The technique employs exactly the same molecular sieve cartridge (MSC) that was tested by Hardie et al (2005) and found not to suffer from fractionation, contamination or sample carry-over effects when used with a pump-based sampling system. Application of the MSC in passive sampling form has already been successfully tested for trapping samples of soil respired CO 2 for 14 C measurement ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, zeolite has a high affinity for polar molecules like CO2. CO2 quadrupole moment interacts with the electric field of zeolite, resulting in high adsorption of CO2 into the zeolite structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Collection of evasion CO 2 samples for isotope analysis and measurement of CO 2 flux rate was achieved by linking a molecular sieve sampling system (Hardie et al 2005) to a floating chamber as described by Billett et al (2006). This recently developed method allows direct collection of the evaded CO 2 and is considered preferable to previously used indirect methods (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Following sample collection, the molecular sieve cartridges were returned to the NERC Radiocarbon Laboratory and the sample CO 2 recovered by heating and cryogenic trapping (see Hardie et al 2005 for details about the molecular sieve procedures).…”
Section: Methodsmentioning
confidence: 99%